Influência da osteoporose e do ácido zoledrônico no desenvolvimento de periodontite apical induzida em ratas - Michelon, Carina (2017)
Osteoporosis is a systemic condition characterized by the reduction of bone mineral density and deterioration of the microarchitecture of the bone tissue, leading to an increase of the bone fragility and, consequently, a greater risk of fracture. Currently, zoledronic acid (ZOL) is one of the drugs most used to treat this systemic disease, since it acts directly on the process of bone remodeling. However, the effects of osteoporosis and systemic therapy with ZOL on the progression of apical periodontitis are not well understood. Thus, the objectives of this study were (1) to evaluate the influence of induced osteoporosis in rats on the progression of apical periodontitis through a systematic review and meta-analysis; (2) to evaluate the effect of osteoporosis and ZOL on the development of periapical lesions in rats using micro-computed tomography (micro-CT). In the systematic review, PubMed, Embase, Web of Science, SCOPUS and LILACS databases were searched up to June 2017. Of 446 potentially eligible, 10 were included in the systematic review. The included outcomes were periapical lesion size and TRAP, RANKL and OPG expressions. Meta-analysis was performed with histometric and radiographic data of the periapical lesion size. For experimental study, 40 female Wistar rats were randomized into four groups (n=10): SHAM – Sham surgery and saline treatment; SHAM-ZOL – SHAM surgery and ZOL treatment; OVX – ovariectomy surgery and saline treatment; OVX-ZOL – OVX surgery and ZOL treatment. The apical periodontitis was inducted on the right mandibular first molar in all animals and saline and ZOL were administered intraperitoneally on the same day. The periapical lesion was measured by radiography and micro-CT. Bone mineral content (BMC) of the femur and mandible was analyzed by computed tomography. According meta-analysis results, induced periapical lesions in rats with osteoporosis are larger than in healthy rats (P < 0.05), both in the global analysis and in the subgroup analyzes for periapical lesion induction time and lineage of rats. In the meta-analysis for x-ray data (mm2), rats with osteoporosis also had larger periapical lesions (P < 0.05). Larger periapical lesions tend to have more elevated expression of TRAP and RANKL. OPG changed in the OVX and SHAM groups according time of induction of periapical lesion; however, there was no pattern of activity. The results of the experimental study showed that there were no statistical difference among the groups in the area and volume of periapical lesions (P > 0.05). BMC in femur’s condyle was significantly lower in the OVX group than in SHAM group (P < 0.05). BMC of the mandible was similar among groups (P > 0.05). In conclusion, the results of this study suggest that osteoporosis plays an important role on the development of apical periodontitis; and that the time of induction of the periapical lesions is the main factor to be considered in this relation. ZOL influences on the systemic BMC, but it appears to have little effect on mandibular bones and on the progression of the periapical lesions at doses used for osteoporosis treatment.